Neuroinflammation and neurodegenerative diseases: Mechanisms, biomarkers and therapeutic interventions. A literature review (Research, Society and Development, 2024)
Introduction: Neuroinflammation is an inflammatory process in the central nervous system that plays a crucial role in neurodegenerative diseases such as Alzheimer's and Parkinson's. This study reviews the literature on the mechanisms of neuroinflammation, biomarkers, and therapeutic interventions. Objective: To review the literature on the mechanisms of neuroinflammation, biomarkers, and therapeutic interventions in neurodegenerative diseases. Methodology: The review covers studies on the activation of glial cells and the release of pro-inflammatory cytokines, as well as the identification of biomarkers in cerebrospinal fluid and blood, and the use of imaging techniques such as PET and MRI. Results: The activation of glial cells and the release of pro-inflammatory cytokines are central to neuroinflammation, contributing to neuronal death. Biomarkers and imaging techniques are essential for the early detection and monitoring of neuroinflammation. Therapeutic interventions include anti-inflammatories, immunomodulators, physical exercise, and diet. Discussion: The interaction between neuroinflammation and other pathological factors, such as oxidative stress and protein aggregation, is an emerging field. Neuroinflammation is not just a secondary response but also a contributing factor to disease progression. Conclusion: Continued research is vital to developing effective interventions and improving patients' quality of life. Interdisciplinary collaboration and translational research are essential to transforming scientific discoveries into practical treatments. Ongoing investments in research can reveal new insights into the pathogenesis of these diseases and develop innovative interventions to slow or prevent neurodegeneration.